Avatar for hotels green training - Ng, Wailing; Hao, Fei; Zhang, Chen (International journal of hospitality management, 2025)
The hospitality industry's shift towards sustainability has necessitated effective green training for employees to ensure the successful implementation of eco-friendly initiatives. This research investigates avatar training as a solution to challenges arising from the scarcity of sustainability trainers. Three between-subject experiments were conducted to understand the influence of avatar attributes—gender (male vs. female), persona (innate vs. incarnate), and value orientation (altruism vs. egoism)—on perceived authenticity, which subsequently influences green engagement, creativity, and Organizational Citizenship Behavior for the Environment. The results consistently highlight a preference for female avatars, with their authenticity perception further amplified when characterized by incarnate avatars or an altruistic value orientation. Theoretically, this study enriches the hospitality literature on technological advancement by innovatively merging the Communication Accommodation Theory with the Ability-Motivation-Opportunity framework. Practically, it equips hoteliers and HR professionals with a groundbreaking training approach, emphasizing the strategic design of avatars to optimize sustainability training outcomes. •Avatar trainers enhance hotel sustainability outcomes, boosting employee green creativity and organizational citizenship.•Female avatars are consistently preferred, elevating the authenticity of green training messages.•Avatar persona and value orientation are pivotal in crafting authentic green trainers.•Integrates Communication Accommodation Theory and Ability-Motivation-Opportunity framework.